2002
DOI: 10.1117/12.452862
|View full text |Cite
|
Sign up to set email alerts
|

Experimental micro-CT system for x-ray NDT

Abstract: This work describes the set-up of an experimental system for micro-tomography developed in the framework of a collaboration between the Physics Department of the University of Bologna (Italy) and the Geosphaera Research Center of Moscow (Russia). The main goal of this inspection system is to carry out high-resolution analysis in vitro of biomedical samples † as well as nondestructive testing (NDT) of industrial components.The detection system consists of a 30x15 mm 2 rectangular fiber-optic taper (ratio 2:1) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The micro-computed tomography (CT) system for small animal imaging has been studied since the 1990s. 10,20,25,29 It can obtain high-resolution anatomical information and be combined with other modalities. 32,33 Micro-CT is a variation of CT and is used primarily for the imaging of bony structure.…”
Section: Introductionmentioning
confidence: 99%
“…The micro-computed tomography (CT) system for small animal imaging has been studied since the 1990s. 10,20,25,29 It can obtain high-resolution anatomical information and be combined with other modalities. 32,33 Micro-CT is a variation of CT and is used primarily for the imaging of bony structure.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to develop a nondestructive test (NDT) of absorbing coatings. At present, common methods of NDT include rays [3], ultrasonics [4], infrared thermography [5] and eddy currents [6]. Among these, infrared thermography has been widely used in NDT due to its advantages of safety, high accuracy and of being non-contact.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, its importance and potential have become increasingly evident even when applied to other areas, such as industry and Cultural Heritage [1]. A growing number of authors have reported the successful use of CT as an efficient and non-destructive tool for the study of, for example, archaeological findings and works of art [2][3][4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%